The evaluation of ADME and pharmacokinetic properties of decoquinate derivatives for the treatment of malaria - Watson, Daniel J.; Laing, Lizahn; Beteck, Richard M.; Gibhard, Liezl; Haynes, Richard K.; Wiesner, Lubbe (Frontiers in Pharmacology, 2022)
The emergence of Plasmodium falciparum (Pf) parasite strains tolerant of the artemisinin component and resistant to the other drug component in artemisinin combination therapies (ACTs) used for treatment now markedly complicates malaria control. Thus, development of new combination therapies are urgently required. For the non-artemisinin component, the quinolone ester decoquinate (DQ) that possesses potent activities against blood stage Pf and acts on a distinct target, namely the Pf cytochrome bc1 complex, was first considered. However, DQ has poor drug properties including high lipophilicity and exceedingly poor aqueous solubility (0.06 μg/mL), rendering it difficult to administer. Thus, DQ was chemically modified to provide the secondary amide derivative RMB005 and the quinoline O-carbamate derivatives RMB059 and RMB060. The last possesses sub-nanomolar activities against multidrug resistant blood stages of Pf, and P. berghei sporozoite liver stages. Here we present the results of ADME analyses in vitro and pharmacokinetic analyses using C57BL/6 mice. The amide RMB005 had a maximum mean whole blood concentration of 0.49 ± 0.02 µM following oral administration; however, the area under the curve (AUC), elimination half-life (t1/2) and bioavailability (BA) were not significantly better than those of DQ. Surprisingly, the quinoline O-carbamates which can be recrystallized without decomposition were rapidly converted into DQ in human plasma and blood samples. The maximum concentrations of DQ reached after oral administration of RMB059 and RMB060 were 0.23 ± 0.05 and 0.11 ± 0.01 µM, the DQ elimination half-lives were 4.79 ± 1.66 and 4.66 ± 1.16 h, and the DQ clearance were 19.40 ± 3.14 and 21.50 ± 3.38 respectively. Under these assay conditions, the BA of DQ could not be calculated Overall although RMB059 and -060 are labile in physiological medium with respect to the DQ parent, the potential to apply these as prodrugs is apparent from the current data coupled with ease of preparation and the difficulty of formulating DQ for use as an antimalarial drug.